Design and analysis of a new six-point edge crack torsion (6ECT) specimen for mode III interlaminar fracture characterisation - Pereira, A.B.
A new six-point edge crack torsion (6ECT) test is proposed for the measurement of the mode III interlaminar critical strain energy release rate GIIIC. In contrast with the common ECT test, which is limited to the evaluation of initiation GIIIC values, the 6ECT allows the measurement of a mode III R-curve. Actually, the existence of such effect has been suggested in various experimental studies. The suitability of the 6ECT carbon/epoxy specimens combined with an effective crack based data reduction scheme is validated by finite element analyses with the virtual crack closure technique and cohesive elements.